The effect of the cultural formulation interview on therapeutic working alliance: a study protocol - Brand, Alma M.; Groen, Simon P. N.; Destoop, Nathalie; Jongsma, Hannah E.; Ghane, Samrad; Sabbe, Bernard G. C.; van Velsen, Harry; van Houten, Kurt; Becan, Özlem; Al Alyan, Dhiya; Braakman, Mario H. (Frontiers in Psychiatry, 2024)
The Cultural Formulation Interview (CFI) is designed to improve understanding of patients' mental health care needs. The lack of empirical evidence on the impact and effectiveness of CFI use in clarifying people's perspectives, experiences, context, and identity, and in preventing cultural misunderstandings between migrant patients and clinicians, inspired this study. The objective is to examine the effect of the CFI on the strength of therapeutic working alliances, and the potential mediating or moderating role of perceived empathy.A multicenter randomized controlled trial will be conducted, involving migrant patients, their confidants, and clinicians. The CFI will be administered in the intervention group, but not in the control group. Validated questionnaires will be used to assess therapeutic working alliances and perceived empathy. T-tests and linear regression analyses will be conducted to investigate between-group differences and possible mediating or moderating effects.Results: This study will indicate whether or not the CFI strengthens the therapeutic working alliance between patients and clinicians, as moderated and/or mediated by perceived empathy.Discussion: Research on the effect and impact of using the CFI in mental health care for migrant patients is important to clarify whether its use strengthens the therapeutic working alliance with clinicians. This can lead to a reduction in cultural misunderstandings and improve mental health care for migrant patients. The results may also be important for the implementation of the CFI as a standard of care.This research protocol was tailored to the needs of patients in collaboration with experts by experience. It was approved by the Ethical Review Board of the Tilburg Law School and registered in the Clinical Trials Register under number NCT05788315. Positive results may stimulate further implementation of the CFI in clinical practice, and contribute to improving the impact of the CFI on the therapeutic working alliances.